Evaluación clínica de la tolerabilidad, seguridad y efectividad antihipertensiva de un extracto estandarizado de Hibiscus sabdariffa (jamaica) en pacientes ambulatorios - Herrera Arellano, Armando (Universidad Autónoma Metropolitana, 2006)
BACKGROUND: With basis on the World Health Organization (WHO) report, the prevalence of hypertension (HT) is of 900 million patients in the world. Mexico contributes with 15.2 million. The treatment of HT is useful to prevent the acute and chronic complications and to reduce mortality. Calyx of the plant species Hibiscus sabdariffa L. (Malvaceae), commonly known as “jamaica” or “flor de jamaica”, is used in different cultures around the world to prepare drinks with antihypertensive properties. Pharmacological tests have demonstrated this effect, probable produced through a diuretic activity and inhibition of angiotensin-converting enzyme (ACE). Recently, we published a clinical trial that confirmed the antihypertensive effect of H. sabdariffa: Patients with HT were daily treated, for 4 weeks, with an infusion of 10 g of dry calyxes of H. sabdariffa in 0.5 L of hot water (containing 9.6 mg of total anthocyanins). Blood pressure (BP) was diminished from 139.05/90.81 to 123.73/79.52 mm Hg. It was also evidenced an increment of the urinary excretion of sodium. At the moment, a phytopharmaceutical, prepared with a dry aqueous extract of H. sabdariffa (standardized on 10 mg of anthocyanins per dose) has been developed. OBJECTIVE: To compare the therapeutic effectiveness, tolerability and safety, as well as, the effect on the serum electrolytes and the inhibitory effect on ACE of the H. Sabdariffa phytopharmaceutical with lisinopril, in patients with stage 1 or 2 HT. SUBJECTS, MATERIAL AND METHODS: Through a randomized, double blind and controlled clinical trial, patients of either sex, with an age of 25 to 61 years old, with diagnosed stage 1 or 2 HT, and without antihypertensive treatment were daily treated, for 4 weeks, with the phytopharmaceutical (experimental group), or with lisinopril 10 mg (control group). Variable outcomes were: therapeutic effectiveness (diastolic blood pressure reduction ≥ 10 mm Hg); (absence of pathological changes in the biochemical tests of hepatic and renal function); tolerability (absence of intense or severe side effects); therapeutic success (all patients at the end of the treatment with therapeutic effectiveness plus tolerability, and safety); changes of the serum electrolytes; and inhibition effect on the ACE. Statistical analysis includes the ANOVA for continuous variables and X2 for the categorical ones; stratified analysis was used for dichotomized confounding variables. Values of p ≤ 0.05 were considered significant. RESULTS: 193 subjects were included (100 in the experimental group), 22 were eliminated because of a lack of treatment adherence and other reasons. Final analysis included 171 subjects (86 in the experimental group), 168 that concludes the study and 3 exclusions; two by hypertensive crisis (one by group); and other one by angioneurotic oedema (in the control group). Basal conditions did not evidence significant differences (p > 0.11) between groups. Results showed that the experimental treatment decreased the BP from 146.48/97.77 to 129.89/85.96 mm Hg, obtaining an absolute reduction of 17.14/11.97 mm Hg and 11.58/12.21 % (ANOVA p < 0.05). Despite the statistical significance, these reductions were lower than that obtained with lisinopril (ANOVA p < 0.05). The outcomes values obtained for experimental and control treatments were as follows: therapeutic effectiveness 65.12 and 82.14% (X2 p = 0.01); tolerability 100 and 98.81% (X2 p = 0.31); safety 100% for both groups, therapeutic successes 65.12 and 81.18% (X2 p = 0.01). On the experimental treatment, the serum chlorine increased from 91.71 to 95.13 mmol/L (ANOVA p = 0.0001), sodium showed a notorious tendency to decrease from 139.09 to 137.35 (ANOVA p= 0.07) while the potassium was not modified. Under the experimental treatment, the plasmatic activity of ACE was inhibited from 44.049 to 30.1 U. (ANOVA p=0.0001), but, when it was compared with the control results, the effect produced by lisinopril was higher (ANOVA p=0.001). The stratified analysis of the experimental group showed that abstemious patients had a higher reduction of BP (X2 p = 0.02). It was also evidenced a higher antihypertensive effectiveness in patients with stage 1 HT (X2 p=0.10). CONCLUSION. The H. Sabdariffa phytopharmaceutical in patients with stage 1 or 2 HT, equal to lisinopril, showed 100% of tolerability and security, in serum increase chlorine and decrease sodium without to modify potassium. Moreover, obtained 65.12% of therapeutic effectiveness and decrease 29.75% the ACE activity, both of magnitude minor than lisinopril.; ANTECEDENTES. Según la Organización Mundial de la Salud (OMS), la prevalencia de la hipertensión arterial sistémica (HAS) es de 900 millones de pacientes en todo el mundo; México aporta 15.2 millones. El tratamiento de la HAS es útil para prevenir las complicaciones agudas y crónicas y reducir la mortalidad. La especie vegetal Hibiscus sabdariffa L. (Malvaceae), se conoce popularmente como “jamaica” o “flor de jamaica”. Su cáliz seco se emplea en diferentes culturas para preparar bebidas con atribuídas propiedades diuréticas e hipotensoras. Diferentes ensayos farmacológicos han evidenciado su efecto hipotensor, ejercido como diurético e inhibidor de la enzima convertidora de angiotensina II (IECA). Recientemente, publicamos un ensayo clínico que corroboró el efecto antihipertensivo de H. sabdariffa: A pacientes con HAS, se les administró diario, durante 4 semanas una infusión de 10 g de cálices secos de H. sabdariffa en 0.5 L de agua caliente (conteniendo 9.6 mg de antocianinas totales). La presión arterial (PA) disminuyó de 139.05/90.81 a 123.73/79.52 mm Hg; además, se evidenció aumento en la eliminación del Na urinario. Actualmente, se ha desarrollado un fitomedicamento con un extracto acuoso seco de cálices de H. sabdariffa, estandarizado en 10 mg de antocianinas. OBJETIVO. Comparar la efectividad, tolerabilidad y seguridad terapéuticas, y el efecto sobre los electrolitos séricos y en la actividad de la ECA plasmática del fitomedicamento de Hibiscus sabdariffa con Lisinopril, en el tratamiento de pacientes con HAS en etapas 1 ó 2. SUJETOS, MATERIAL Y METODOS. Diseño: Ensayo clínico aleatorizado, doble ciego y controlado. Sede: Hospital General Regional del IMSS en Cuernavaca, Morelos. Sujetos: hombres y mujeres, edad de 25 a 61 años, con diagnóstico de HAS etapa 1 y 2, sin tratamiento farmacológico. Intervenciones: Experimental, Control, lisinopril 10 mg. Ambos medicamentos se presentaron en sobres individuales. Posología: diluir el contenido de un sobre en un vaso de agua fría y tomar diario, durante 4 semanas continuas. Desenlaces: Efectividad terapéutica (reducción de la PA diastólica ≥ 10 mm Hg); seguridad (ausencia de cambios patológicos en las pruebas bioquímicas de función hepática y renal); tolerabilidad (ausencia de reacciones adversas intensas o severas); éxito (al final del tratamiento deben coincidir tolerabilidad, seguridad y efectividad terapéuticas); cambios en los electrolitos séricos; y en la actividad de la ECA plasmática. Seguimiento: semanal, durante 4 semanas. Análisis de datos: prueba de ANOVA para las variables continuas y Chi2 para las categóricas; análisis estratificado con variables confusoras dicotomizadas. Valores de p ≤ 0.05 se emplearon para rechazar hipótesis de igualdad. RESULTADOS. Ingresaron al estudio 193 sujetos (100 en el grupo experimental), se excluyeron 22 sujetos por falta de apego y por otros motivos. El análisis final incluyó 171 sujetos (86 en el grupo experimental), 168 que concluyeron el estudio y 3 exclusiones; dos por urgencia hipertensiva (uno por grupo) y otro por edema angioneurótico (en el grupo control). En condiciones basales las variables evaluadas no presentaron diferencias significativas (p > 0.11). Al final del estudio, el tratamiento experimental disminuyó la PA de 146.48/97.77 a 129.89/85.96 mm Hg, logrando una reducción absoluta de 17.14/11.97 mm Hg y porcentual de 11.58/12.21 % (ANOVA p < 0.05); sin embargo, estas reducciones fueron menores que las obtenidas con lisinopril (ANOVA p < 0.05). Los desenlaces con los tratamientos experimental y control fueron: efectividad terapéutica 65.12 y 82.14% (Chi2 p = 0.01); tolerabilidad 100 y 98.81% (Chi2 p = 0.31); seguridad 100% en ambos grupos, éxitos terapéuticos 65.12 y 81.18% (Chi2 p = 0.01). Con el tratamiento experimental, el cloro sérico aumentó de 91.71 a 95.13 mmol/L (ANOVA p = 0.0001), el sodio mostró franca tendencia a disminuir de 139.09 a 137.35 (ANOVA p = 0.07) y el potasio no se modificó. Bajo el tratamiento exprimental la actividad de ECA plasmática se redujo de 44.049 a 30.1 Us (ANOVA p=0.0001); al compararla con la obtenida con el control, existieron diferencias a favor de lisinopril (ANOVA p = 0.0001). El análisis estratificado del grupo experimental, mostró que los no alcohólicos redujeron más la PA que los alcohólicos (Chi2 p = 0.02), así como tendencia a mayor efectividad terapéutica en los pacientes que ingresaron con HAS en etapa 1 (Chi2 p = 0.10). CONCLUSIÓN. El fitofármaco de H. sabdariffa en pacientes con HAS etapas 1 y 2, igual que el lisinopril, mostró tolerabilidad y seguridad del 100% y en suero aumentó el cloro y redujo el sodio sin modificar el potasio. Además, logró 65.12% de efectividad terapéutica y redujo 29.75% la actividad de la ECA, ambos de menor magnitud que lisinopril.